2021
DOI: 10.3390/antibiotics10070857
|View full text |Cite
|
Sign up to set email alerts
|

The Epistatic Landscape of Antibiotic Resistance of Different Clades of Mycobacterium tuberculosis

Abstract: Drug resistance (DR) remains a global challenge in tuberculosis (TB) control. In order to develop molecular-based diagnostic methods to replace the traditional culture-based diagnostics, there is a need for a thorough understanding of the processes that govern TB drug resistance. The use of whole-genome sequencing coupled with statistical and computational methods has shown great potential in unraveling the complexity of the evolution of DR-TB. In this study, we took an innovative approach that sought to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…We used the method proposed by Muzondiwa et al ( 8 ) to assess the risk of different orders of paired resistance ( Fig. 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the method proposed by Muzondiwa et al ( 8 ) to assess the risk of different orders of paired resistance ( Fig. 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of a highly conserved pattern of SNPs in dop of pathogenic mycobacteria [ 60 ], in serial isolates comparisons we observed non-synonymous variants within codons 7, 18, and 37, different from those which were described as undergoing mutational shifts with high rates [ 60 ]. A recent study showed that SNP within 37 codon of dop gene was epistatically linked to resistance-associated loci katG :315 and embB :296 in Beijing isolates [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rifampin (RIF) rpoB rpoA, rpoC (Telenti et al, 1993;Ohno et al, 1996;Ramaswamy and Musser, 1998;Comas et al, 2011;Shea et al, 2021) Pyrazinamide (PZA) pncA pnaB2 (epistatic) (Konno et al, 1967;Scorpio and Zhang, 1996;Muzondiwa et al, 2021) Para-aminosalicylic acid (PAS) thyA thyX-hsdS.1 intergenic region associated, but not shown to be compensatory (Rengarajan et al, 2004;Zhang et al, 2013;Coll et al, 2018) Ethambutol (EMB) embCAB operon aftA (Rv3792) (Alcaide et al, 1997;Telenti et al, 1997;Safi et al, 2013) Isoniazid (INH) katG, inhA ahpC promoter (Zhang et al, 1992;Heym et al, 1995;Sherman et al, 1996) Fluoroquinolones (FQ) gyrA Extragenic Rv0890c, Insertions in glgC in Mycobacterium aurum (Takiff et al, 1994;Pi et al, 2020) Bedaquiline (BDQ) mmpR (Rv0678), atpE, pepQ atpB? (suggested) (Andries et al, 2005;de Jonge et al, 2007;Huitric et al, 2010;Andries et al, 2014;Nieto Ramirez et al, 2020) Clofazimine (CFZ) pepQ, mmpR Unknown (Almeida et al, 2016) Pretomanid (PA-824)/ Delaminid (DLM)…”
Section: Compensatory Mechanism Referencesmentioning
confidence: 99%